VD_FINDINFO HC / 2017 / 1127 vom 15. November 2017 - VD Tribunal cantonal (2017)
DÉPENS, PREUVE À FUTUR, DROIT D'ÊTRE ENTENDU | 29 al. 2 Cst., 105 al. 2 CPC (CH), 110 CPC (CH), 319 let. b ch. 1 CPC (CH), 3 TDC